2015
DOI: 10.1016/j.virol.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactis displayed neuraminidase confers cross protective immunity against influenza A viruses in mice

Abstract: Influenza A viruses pose a serious threat to public health. Current influenza A vaccines predominantly focus on hemagglutinin (HA) and show strain-specific protection. Neuraminidase (NA) is much less studied in the context of humoral immunity against influenza A viruses. The purpose of this study is to evaluate the cross protective immunity of NA presented on Lactococcus lactis (L.lactis) surface against homologous and heterologous influenza A viruses in the mouse model. L.lactis/pNZ8110-pgsA-NA was constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…To overcome these hurdles, as a powerful technology, surface display may be a good choice to express heterogeneous peptides and proteins on cells, making use of natural functional components of microorganisms (Raha et al 2005;Kuczkowska et al 2016). Poly-γ-glutamic acid synthetase A (pgsA), which is a constituent protein of the polyglutamate synthetase system (PGA) of Bacillus subtilis, has been widely used to anchor foreigner protective antigens on the surface of lactic acid bacteria (Sewaki 2010;Lei et al 2015). In previous studies, we successfully used surface display technology to express a number of targeted proteins, such as hemagglutinin subunit 2 (HA2) of avian influenza virus (AIV), and murine IL-10 and spike protein (S) of porcine epidemic diarrhea virus (PEDV) (Cai et al 2016;Huang et al 2017;Jiang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these hurdles, as a powerful technology, surface display may be a good choice to express heterogeneous peptides and proteins on cells, making use of natural functional components of microorganisms (Raha et al 2005;Kuczkowska et al 2016). Poly-γ-glutamic acid synthetase A (pgsA), which is a constituent protein of the polyglutamate synthetase system (PGA) of Bacillus subtilis, has been widely used to anchor foreigner protective antigens on the surface of lactic acid bacteria (Sewaki 2010;Lei et al 2015). In previous studies, we successfully used surface display technology to express a number of targeted proteins, such as hemagglutinin subunit 2 (HA2) of avian influenza virus (AIV), and murine IL-10 and spike protein (S) of porcine epidemic diarrhea virus (PEDV) (Cai et al 2016;Huang et al 2017;Jiang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Given the characteristics of the pgsA protein, it has been applied to a variety of prokaryotic protein surface displays. In particular, it has been successfully applied in Gram-positive receptor strains such as lactic acid bacteria, which provide a theoretical basis for us to study how to anchor exogenous proteins on the cell wall surface of Lactobacillus plantarum (Lei et al 2015;Yang et al 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…rNA vaccines are capable of inducing NI antibodies that have been reported to suppress viral replication and disease in experimental animals (Deroo et al, 1996; Kilbourne et al, 2004). Lei et al recently showed that NA presented on the surface of Lactococcus lactis provided protection against highly pathogenic avian influenza (HPAI) H5N1 virus in mice (Lei et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Usually it is considered that the cell surface anchored antigen and secreted antigen could induce much stronger immune responses compared with the intracellular production of desired antigen due to the higher degree of exposure of the antigen to the host. Our lab has recently used the anchoring sequence from poly-γ-glutamic acid synthetase A (pgsA), a transmembrane protein from Bacillus subtilis [11][12][13] in order to construct recombinant L. plantarum strains capable in expressing foreign antigens. The resulting strains were efficient in the production of protective antibody responses and partial protection against either influenza virus [14], transmissible gastroenteritis virus [15,16] or porcine epidemic diarrhea virus [17].…”
mentioning
confidence: 99%